Kinship and Intimate Partner Violence Against Married Women in Ghana: A Qualitative Exploration - Sedziafa, A.P.; Tenkorang, E.Y.; Owusu, A.Y. (SAGE Publications Inc., 2018)
In African societies, kinship ties determine how women are socialized, their access to power and wealth, as well as custody of children, often considered important factors in married women’s experience of intimate partner violence (IPV). Yet studies that examine how kinship norms influence IPV are scant. Using in-depth interviews collected from women identifying with both matrilineal and patrilineal descent systems, we explored differences in Ghanaian women’s experiences of IPV in both kin groups. Results show that while IPV occurs across matrilineal and patrilineal societies, all women in patrilineal societies narrated continuous pattern of emotional, physical, and sexual assault, and their retaliation to any type of violence almost always culminated in more experience of violent attacks and abandonment. In matrilineal societies, however, more than half of the women recounted frequent experiences of emotional violence, and physical violence occurred as isolated events resulting from common couple disagreements. Sexual violence against matrilineal women occurred as consented but unwanted sexual acts, but patrilineal women narrated experiencing violent emotional and physical attack with aggressive unconsented sexual intercourse. Contextualizing these findings within existing literature on IPV against women suggests that policies aimed at addressing widespread IPV in Ghanaian communities should appreciate the dynamics of kinship norms. © 2016, The Author(s) 2016.
Keywords: culture; gender; Ghana; intimate partner violence; kinship